Characterization of metallocene ethylene-1-octene copolymers with high comonomer content cross-linked by dicumyl peroxide or β-radiation - Nicolas, Julieta (2009)
Two metallocene ethylene-1-octene copolymers differing in comonomer content were cross-linked either by dicumyl peroxide (DCP) or β-radiation with doses ranging from 0.5 to 4% DCP and 25 to 200 kGy, respectively. The effect of cross-linking on the crystalline morphology was analyzed by differential scanning calo-rimetry (DSC). Slight alterations in the crystalline structure were found, which were more severe in the case of peroxi modification. Through infrared spectroscopy (FTIR analysis), oxidation during the cross-linking process was detected on the DCP cross-linked samples, while β-irradi-ated samples do not exhibited significant degrees of oxidation. The state of cure was studied following the changes in the Theological properties in small-amplitude oscillatory shear mode, and the evolution of the molecular weight and molecular weight distribution through size exclusion chromatography. Irradiation doses below 200 kGy increased the molecular weight and branching of both copolymers but were not sufficient to reach gelation. All the peroxide modified samples resulted in a post-gel condition. Optimal mechanical properties were obtained with concentration of about 1% DCP. At higher doses, scission reactions diminish the tensile strength and the elongation at break. When polymers with equivalent amounts of gel fraction obtained by the two modification procedures studied in this work are compared, higher tensile strength and elongation at break are obtained with irradiation. © 2009 Wiley Periodicals, Inc.